2012
DOI: 10.1016/j.jacc.2011.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arterial 18F-Sodium Fluoride Uptake

Abstract: 18F-NaF is a promising new approach for the assessment of coronary artery plaque biology. Prospective studies with clinical outcomes are now needed to assess whether coronary 18F-NaF uptake represents a novel marker of plaque vulnerability, recent plaque rupture, and future cardiovascular risk. (An Observational PET/CT Study Examining the Role of Active Valvular Calcification and Inflammation in Patients With Aortic Stenosis; NCT01358513).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
189
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 442 publications
(202 citation statements)
references
References 41 publications
10
189
0
3
Order By: Relevance
“…Several other studies have reported similar findings and have led to growing support for the use of 18 F‐NaF for imaging the process of microcalcification and visualizing ongoing mineral deposition within the atherosclerotic plaque 64, 99, 100, 101, 102, 103…”
Section: Positron Emission Tomographymentioning
confidence: 64%
See 4 more Smart Citations
“…Several other studies have reported similar findings and have led to growing support for the use of 18 F‐NaF for imaging the process of microcalcification and visualizing ongoing mineral deposition within the atherosclerotic plaque 64, 99, 100, 101, 102, 103…”
Section: Positron Emission Tomographymentioning
confidence: 64%
“…Dweck et al64 observed that in spite of a strong correlation between 18 F‐NaF uptake and CACS ( r =0.652, P <0.001), there was no corresponding 18 F‐NaF uptake in many of the densely calcified regions on CT. In fact, 41% of patients with CACS >1000 had no significant 18 F‐NaF uptake, and often 18 F‐NaF uptake was found in areas adjacent to and remote from existing coronary calcification.…”
Section: Positron Emission Tomographymentioning
confidence: 98%
See 3 more Smart Citations